A fiscal theory of sovereign risk - Martín Uribe (European Central Bank (ECB), 2002)
This paper presents a fiscal theory of sovereign risk and default. Under certain monetary-fiscal regimes, the risk of default, and thus the emergence of sovereign risk premia, are inevitable. The paper characterizes the equilibrium processes of the sovereign risk premium and the default rate under a number of alternative monetary policy arrangements. It is argued that, given the fiscal stance, monetary policy plays a crucial role in shaping the equilibrium behaviour of the country risk premium and the default rate. For instance, under some of the monetary policy rules considered, the expected default rate and the sovereign risk premium are zero (and therefore unforecastable) although the government defaults regularly. Under other monetary regimes the default rate and the sovereign risk premium are serially correlated (and therefore forecastable). In addition, environments are characterized under which delaying default is counterproductive.
Keywords: E6; F4; 330